Meta-Geopolitics of Outer Space - Al-Rodhan, N. author. aut Link
IX, 276 p.
Keywords: Al-Rodhan sheds new light on the debate about the geopolitics of outer space, going beyond applying traditional International Relations approaches to space power and security by introducing a multidimensional spatial framework. The meta-geopolitics framework includes space and expands classical power considerations to cover seven state capacities.